Ice Conditions Along the Illinois Waterway as Observed on Landsat Images, 1972-1985 - Gatto, Lawrence W. (1989)
Landsat images were used to map ice distributions along the navigable portions of the Illinois Waterway from the Mississippi River to Lake Michigan, and air temperature and discharge data were used to characterize the conditions under which the observed ice formed and changed. The presence or absence of ice on adjacent water bodies, i.e., lakes, channels and sloughs, is also discussed but not mapped. Ice was observed on the waterway during 10 of the 13 winters from 1972 to 1985, with the most severe ice conditions in 1981-82 when 79% of the waterway was ice covered, of which 68% was white ice on 4 February. The most extensive ice was observed during 1984-85 when 83% of the waterway was ice covered, but only 38% was white ice. Ice was observed on the adjacent water bodies every winter for about 100 days from early to mid-December to mid-March. Ice conditions changed frequently on the navigation channel of the waterway and usually lasted an average of 63 days from middle to late December to middle to late February. Air temperature and discharge data and data from Landsat images, when used together, provide a reasonably reliable method to study river ice conditions and changes. (edc)